Pengembangan Bahan Ajar Modul Biologi pada Materi Metode Ilmiah di Kelas X SMA Negeri 2 Pangkalan Bun - Yula Miranda; Evita Waindriyani (Jurnal Ilmiah Kanderang Tingang, 2023)
The purpose of writing this article is to assess the feasibility of biology teaching materials (learning modules) in the Scientific Method material for class X SMA This study uses a quasi-experimental method. The research design uses a one group pretest-posttest design. Test the effectiveness of the module using a one group pretest-posttest design only which involves 54 students of class X MIPA class of 2022/2023. Observations made at Pangkalan Bun 2 Public High School in biology subjects, it was found that the scientific method material contained misconceptions so researchers needed to develop teaching materials related to the scientific method. The feasibility of the material in teaching materials (learning modules) is evaluated at three stages of development, namely initial investigation, curriculum analysis, concept analysis, and at the same time this research also ensures the feasibility of the modules that have been developed. The results of the pretest and posttest analysis given to the treatment class showed an increase in the completeness score of 66.67%. The class given the implementation of the scientific method module experienced an increase in value from 11.11% to 77.78%. Data analysis using N- Gain shows the class where the scientific method module is implemented shows an N-Gain score of 0.32 which indicates a medium category n-Gain value, even though the N-Gain effectiveness category obtained shows a percentage of 52.56% indicating less effective . This shows that the biology module material for scientific method is quite feasible to use.